Project Based Learning: Development of Taxiway Light as a Visual Landing Aid Using Solar Power - Soleh, Asep Muhamad; Callista, Annisa Baby; Maulana, Moch. Yosfika Agung (Graduate Program Magister Manajemen Pendidikan, 2024)
This research aims to determine the differences in learning methods in the classroom using project-based learning and conventional learning. The research was carried out using quantitative methods by conducting evaluations and interviews with cadets. Data processing uses the Manova test statistical data processing application. The sample from this research was Palembang Aviation Polytechnic cadets in visual aid courses, especially taxiway lights. From the results of data processing, we can see differences in terms of creativity and learning outcomes between cadets who use project-based learning methods and those who use conventional learning systems. Project-based learning methods have fostered creativity and better learning outcomes. Hopefully with the results of this research, lecturers will more often use project-based learning methods to foster the creativity of Aviation Polytechnic cadets within the Ministry of Transportation of Indonesia.